The Experimentally Justified Opportunity of Psychological Imitation by Primary School Children of Moderators' Merciful Behavior - Solovyova, Tatiana; Guseva, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article theoretically and empirically examines the possibility for psychological imitation of moderators’merciful behavior by schoolchildren. The conclusions have been drawn on the basis of the questionnaire analysis, field-proven reliability and internal consistency by means of SPSS Statistics. The authors have come to the following conclusions: firstly, primary school moderators do not always show an example of compassionate behavior to their disciples; secondly, moderators need to rethink their life position and the opportunity to correct it in order to reveal a perfect example of compassionate behavior for children; thirdly, the moderator should monitor his behavior in front of the children and manage negative emotions working with the pupils; finally, the moderators’ level of personal aggressiveness  should be checked during his professional assessment test.